Volatile DBPs contributed marginally to the developmental toxicity of drinking water DBP mixtures against Platynereis dumerilii. (August 2020) - Li, Yu; Jiang, Jingyi; Li, Wanxin; Zhu, Xiaohu; Zhang, Xiangru; Jiang, Feng
Abstract: Halogenated disinfection byproducts (DBPs) are formed during chlorine disinfection of drinking water. The complicated natural organic matter in source water causes the formation of an even more complicated mixture of DBPs. To evaluate the toxicity of a DBP mixture in a disinfected water sample, the sample needs to be pretreated in order to attain an observable acute adverse effect in the toxicity test. During sample pretreatment, volatile DBPs including trihalomethanes, haloacetonitriles and haloketones may be lost, which could affect the toxicity evaluation of the DBP mixture. In this study, we intentionally prepared "concentrated" simulated drinking water samples, which contained sufficiently high levels of volatile and nonvolatile DBPs and thus enabled directly evaluating the toxicity of the DBP mixtures without sample pretreatment. Specifically, the natural organic matter and bromide concentrations and the chlorine dose in the concentrated water samples were 250 times higher than those in a typical drinking water sample. Each concentrated water sample was divided into two aliquots, and one of them was nitrogen sparged to eliminate volatile DBPs; then, both aliquots were used directly in a well-established developmental toxicity test. No significant difference ( p > 0.10) was found between the developmental toxicity indexes of each concentrated water sample without and with nitrogen sparging, indicating that the contribution of volatile DBPs to the developmental toxicity of the DBP mixture might be marginal. A reasonable interpretation is that nonvolatile halogenated DBPs (especially the aromatic ones) in the DBP mixture could be the major developmental toxicity contributor that warrants more attention. Graphical abstract: Image 1 Highlights: Concentrated water samples were prepared with high concentrations of NOM, bromide and chlorine. Nitrogen sparging removed 98.5–99.7% of volatile DBPs in the concentrated water samples. No significant difference in developmental toxicity was found for each sample without and with N2 sparging. The contribution of volatile DBPs to the developmental toxicity of DBP mixtures was marginal.